2016
DOI: 10.1189/jlb.1ta1115-517rr
|View full text |Cite
|
Sign up to set email alerts
|

Technical Advance: Changes in neutrophil migration patterns upon contact with platelets in a microfluidic assay

Abstract: Neutrophils are traditionally regarded as the "first responders" of the immune system. However, recent observations revealed that platelets often respond earlier to recruit and activate neutrophils within sites of injury and inflammation. Currently, platelet-neutrophil interactions are studied by intravital microscopy. Although such studies provide exceptional, physiologic in vivo data, they are also laborious and have low throughput. To accelerate platelet-neutrophil interaction studies, we have developed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Platelet activation has also been widely reported in sepsis 2527 and has been suggested as a candidate rapid-response element during disease 28 . A previous study by some of the authors of this work demonstrated that activated platelets could induce spontaneous neutrophil motility and oscillatory motility patterns 29 . While no single factor has yet been identified that can accurately stratify sepsis from non-sepsis, in combination, these responses likely contribute to the specific neutrophil spontaneous motility signatures that we capture using the whole blood assay presented here.…”
Section: Discussionmentioning
confidence: 59%
“…Platelet activation has also been widely reported in sepsis 2527 and has been suggested as a candidate rapid-response element during disease 28 . A previous study by some of the authors of this work demonstrated that activated platelets could induce spontaneous neutrophil motility and oscillatory motility patterns 29 . While no single factor has yet been identified that can accurately stratify sepsis from non-sepsis, in combination, these responses likely contribute to the specific neutrophil spontaneous motility signatures that we capture using the whole blood assay presented here.…”
Section: Discussionmentioning
confidence: 59%
“…In platelet-depleted mice, or when the PSGL-1 interaction with its receptor on neutrophils was blocked, the neutrophil typical crawling was suppressed (42). These results were further validated by a novel ex vivo microfluidic system that allowed a better understanding of the interaction between these two cells types and the importance of the P-selectin and PSGL-1 (P-selectin glycoprotein ligand-1) in that context (48). Curiously, this same interaction also leads to the generation of neutrophil-derived vesicles filled with arachidonic acid, which are promptly internalized by platelets via Mac-1.…”
Section: Platelet Roles In Immune Cell Migration Phagocytosis and Pamentioning
confidence: 83%
“…We used fMLP as a platelet chemoattractant here because it has been reported to induce robust platelet chemotaxis and is pertinent to host defence being a constituent of bacterial cell walls, but has not been described to induce platelet aggregation (Czapiga et al, 2005). We have also investigated PINC, akin to in vivo neutrophil intravascular crawling, that has previously been optimized in vitro to investigate interactions between platelets and neutrophils at the single cell level under precise conditions that are platelet P-selectin dependent (Bengtsson et al, 1999;Kornerup et al, 2010;Amison et al, 2015), and using microfluidic assays (Frydman et al, 2017;Rainger et al, 1997). Here, we used MDC as the chemotactic substance, because it has been shown to activate platelets via the activation of CCR4 receptors, and is highly expressed during LPS induced neutrophilic inflammation with no associated thrombosis or changes to haemostasis (Kornerup et al, 2010;Amison et al, 2017b;Clemetson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%